Greenwashing and Information Asymmetry: A Theoretical Perspective (European Journal of Marketing and Economics, 2026)
Greenwashing has emerged as a growing concern in contemporary markets, where firms increasingly communicate environmental commitments as part of their competitive positioning. While existing literature documents the prevalence and consequences of misleading environmental claims, limited theoretical integration explains why greenwashing persists despite reputational and regulatory risks. This paper conceptualizes greenwashing as a signaling failure under conditions of information asymmetry. Drawing on information economics and signaling theory, we develop a theoretical framework that explains the strategic incentives driving firms to engage in symbolic environmental communication. The model highlights the role of verification costs, consumer environmental literacy, and institutional pressures in shaping market outcomes. We propose a set of theoretical propositions linking greenwashing to consumer trust erosion, market inefficiencies, and long-term legitimacy risks. The paper contributes by integrating fragmented streams of research and offering a structured framework to guide future empirical studies. Managerial and policy implications are discussed.
Keywords: Greenwashing, green marketing, consumer behavior, environmental communication, consumer trust.